2021
DOI: 10.1590/1413-7054202145008221
|View full text |Cite
|
Sign up to set email alerts
|

Physical, biochemical, and sensory properties of strawberries grown in high-altitude tropical climate

Abstract: New cultivars generated each year by international breeding programs enter the Brazilian market. These cultivars need to be tested for their adaptation to the climate in each environment due to the great variety of climates that exist in the country. Strawberry is a highly appreciated fruit due to its biochemical and sensory characteristics and is considered the most important berry. The objective of this study was to determine the physical, biochemical, and sensory properties by performing a sensory evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 76 publications
0
1
0
2
Order By: Relevance
“…Principal component analysis (PCA) allows us to extract important information from a data set containing multiple inter-correlated quantitative variables. This is possible since it reshapes data along principal component axes, reducing their dimensionality in an interpretable way [1,36]. The PCA showed that most of the variance (76.53%) was explained by the two first components.…”
Section: First Experiment: Evaluation and Selection Of Strawberry Gen...mentioning
confidence: 99%
“…Principal component analysis (PCA) allows us to extract important information from a data set containing multiple inter-correlated quantitative variables. This is possible since it reshapes data along principal component axes, reducing their dimensionality in an interpretable way [1,36]. The PCA showed that most of the variance (76.53%) was explained by the two first components.…”
Section: First Experiment: Evaluation and Selection Of Strawberry Gen...mentioning
confidence: 99%
“…A quantidade de açúcares nos frutos consiste principalmente de açúcares, e varia com a espécie, cultivar, estágio de maturação e clima (PINHEIRO et al, 2021). O grau de doçura da fruta é prejudicado por pressões ambientais que reduzem a sacarose e o Brazilian Journal of Development, Curitiba, v.9, n.5, p. 14839-14846, may., 2023 conteúdo volátil total (COZZOLINO et al, 2021).…”
Section: Introductionunclassified
“…Porém é visto de que ocorrem diferenças nas análises químicas em se tratando de diferentes cultivares. Os perfis entre as variedades comerciais de morango são complexos e em sua maioria são distintos (PINHEIRO et al, 2021). Diante disto, o presente estudo teve por objetivo analisar as características físico-químicas de seis diferentes cultivares de morangueiro, cultivados sob as mesmas condições, quantificando à diferença entre teores de pH, sólidos solúveis, acidez total titulável bem relação sólidos solúveis totais/acidez total titulável.…”
Section: Introductionunclassified